2022
DOI: 10.3389/fpsyt.2022.893861
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction in young adults: The role of impulsivity and codependency

Abstract: Excessive Internet use has demonstrated comorbidity with other psychological symptoms and psychiatric disorders, as well as impairments in the management of daily life, relationships and emotional stability. Recent findings in the literature have consistently supported the relationship between impulsivity and Internet addiction. The present study hypothesized that, in addition to impulsivity, a further predictor of Internet addiction might be relational co-dependency, which is also associated in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 153 publications
(143 reference statements)
0
23
0
Order By: Relevance
“…Several studies highlighted the significant and lasting impact of personal limitations due to the pandemic condition on wellbeing and the mental health of individuals of all age groups, but also especially in young people. More specifically, an increase in stress, worry, insomnia, disorientation, pessimism, obsessive-compulsive symptoms and even gambling disorders has been reported [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlighted the significant and lasting impact of personal limitations due to the pandemic condition on wellbeing and the mental health of individuals of all age groups, but also especially in young people. More specifically, an increase in stress, worry, insomnia, disorientation, pessimism, obsessive-compulsive symptoms and even gambling disorders has been reported [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, IA and suicide, and self-injury behaviors are considered addictive [69,70]. Adolescents with IA may be unable to control impulsivity, and those with negative coping styles are more likely to rely on the internet [71][72][73]. Furthermore, IA may damage cognitive function in adolescents [74].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies have shown that people will communicate with others online and use their smartphones more frequently to feel satisfied, raising the risks of SMA (Zhao et al, 2021;Diotaiuti et al, 2022). Lai et al (2022), on the other hand, asserted that SMA is a predictor of PHUB in a sample of Chinese HE students.…”
Section: Smartphone Addiction and Phubbing Headingsmentioning
confidence: 99%